An In Vitro Comparison of Microbial Ingress Into 8 Different Needleless IV Access Devices. Issue 1 (January 2015) - Casey, Anna; Karpanen, Tarja; Nightingale, Peter; Elliott, Tom
<x xml:space="preserve">Abstract</x> There are conflicting reports of the effect needleless intravenous access devices have on rates of catheter-related bloodstream infection. The aim of this study was to identify any differences between the rates of microbial ingress into 8 different devices following contamination. Each type of device was subjected to a 7-day clinical simulation that involved repeated microbial contamination of the injection site and decontamination followed by saline flushes. Significant differences in the number of microorganisms associated with each device were detected in the saline eluates. Three positive-displacement mechanical valves were associated with the ingress of significantly fewer microorganisms compared with other devices.